Development of trigonometric comparison teaching materials based on ICT and Tri-N for face-to-face and distance learning - Ayung Yeni Prihatin; I Nyoman Arcana; Betty Kusumaningrum (Universitas Sarjanawiyata Tamansiswa, 2024)
This study endeavors to (1) develop instructional materials grounded in ICT and Tri-N principles tailored for both Face-to-Face Learning and Distance Learning modalities, and (2) assess the feasibility of these materials for dual usage. The research methodology employed is the Research and Development (R&D) approach, utilizing the ADDIE model encompassing five sequential stages: (1) Analysis; (2) Design; (3) Development; (4) Implementation; and (5) Evaluation. The study was conducted at SMA N 5 Yogyakarta, with a cohort of 36 students from class X-1 utilizing the PTM model, and another 36 students from class X-2 employing the PJJ model as research subjects. Data collection methods encompassed validation questionnaires, student response surveys, and learning outcome assessments, while data analysis involved both qualitative and quantitative descriptive methodologies. The research culminated in the creation of instructional materials rooted in ICT and Tri-N principles, comprising videos, PowerPoint (PPT) presentations, and handouts, which underwent comprehensive product feasibility testing. Validation results from media and material experts demonstrated a high level of validity, with Face-to-face instructional materials receiving an average score of 4.55 and distance learning instructional materials achieving an average score of 4.04. During the implementation phase, student feedback yielded favorable average scores of 3.49 for face-to-face instructional materials and 4.02 for distance instructional materials, indicating positive reception and usability. Notably, statistical analyses revealed a significant positive correlation between student responses and learning outcome assessments, affirming the suitability of the instructional materials for effective utilization by both students and educators.